Reliability and validity of the Modified Dental Anxiety Scale (MDAS) in a Turkish population - Tunc EP, Firat D, Onur OD, Sar V. (Blackwell Synergy, 2005)
Fear of dentistry is a common obstacle to obtaining dental care in Turkey.